1999
DOI: 10.1016/s0168-1923(99)00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration model for semi-arid shrub-lands tested against data from SE Spain

Abstract: A model was developed that predicted evaporation based on combined information on the physiology of overstorey and substrate, micrometeorological conditions and spatial distribution of plants. Predicted evapotranspiration was veri®ed at stand level for Retama sphaerocarpa shrubs, and model parameters were tested to determine their importance in controlling evaporation. Model predictions were compared with evapotranspiration, measured by a Bowen Ratio Energy Balance system (BREB), and transpiration, measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 36 publications
2
78
0
2
Order By: Relevance
“…Moreover, VPD under shrubs was about half that in open interspaces. These environmental changes can improve the water status of saplings even in the absence of between-microhabitat differences in soil water content, as happened in this study (Holmgren et al 1997;Domingo et al 1999). Although microclimatic differences between microhabitats were not evaluated in winter, shrubs presumably also ameliorate negative temperatures, reducing the risk of frost damage to tissues (Kikvidze & Nakhutsrishvili 1998;Núñez et al 1999).…”
Section: Facilitation Of Sapling Survival: the Role Of Microhabitat Amentioning
confidence: 68%
“…Moreover, VPD under shrubs was about half that in open interspaces. These environmental changes can improve the water status of saplings even in the absence of between-microhabitat differences in soil water content, as happened in this study (Holmgren et al 1997;Domingo et al 1999). Although microclimatic differences between microhabitats were not evaluated in winter, shrubs presumably also ameliorate negative temperatures, reducing the risk of frost damage to tissues (Kikvidze & Nakhutsrishvili 1998;Núñez et al 1999).…”
Section: Facilitation Of Sapling Survival: the Role Of Microhabitat Amentioning
confidence: 68%
“…(9) fitted the results best. In previous studies (McInnes et al 1994;Domingo et al 1999), a power function was used, but it was found that this approach considerably overestimated r a measured at our site, at low wind speeds.…”
mentioning
confidence: 60%
“…The technical characteristics of SBIB probes, their calibration as well as successful results with replicates of the same prototype used in different soils, are detailed in different publications (Puigdefábregas et al, , 1998Vidal et al, 1996;Domingo et al, 1999Domingo et al, , 2001Cantón et al, 2001Cantón et al, , 2004. Beginning in July 2003, six probes were installed in a 10 Â 10 m area the eddy tower at a depth of 0.06 m. Moreover, at the end of 2003, six additional y probes were installed in the same place at two depths (three at a depth of 0.06 m and three more at 0.25 m depth), such that y data at two depths are available only from 12 February 2004 to 31 August 2005.…”
Section: Field Measurementsmentioning
confidence: 99%
“…on the first five days in June, and at 0.25 m only reached 9 %vol. In nearby areas with similar climate, the maximum E occurs in May (Domingo et al, 1999). The seasonal pattern of variation in y, high in spring and late autumn and characteristically low in summer when plants actively take up soil water, is well known (Henninger et al, 1976;Ehrenfeld et al, 1997;Gehrels et al, 1998).…”
Section: Dynamics Of Water Balance Componentsmentioning
confidence: 99%